Ulama dan Politik: Keterlibatan Ulama Sumatera Selatan dalam Politik Praktis dan Community Empowerment Pada Abad XX - Nurseri Hasnah Nasution (Jurnal Studi Sosial dan Politik, 2017)
The cleric of South Sumatra is a central figure who has a very wide authority. They have a multifunction with polymorphic leadership. Historical facts show that they are civilization actors who respond to various problems of South Sumatra in the twentieth century. These problems are characterized by the religious phenomenon of postmodernism and the problems of religious articulation diversity. To respond to these phenomena and problems, some South Sumatra clerics such as K.H. Anwar Kumpul, K.H. M. Zen Syukri, K.H. Zainal Abidin Fikry is actively involved in practical politics and community empowerment. K.H. Anwar Kumpul, K.H. M. Zen Syukri, K.H. Zainal Abidin Fikry actively participates in practical politics, has a spirit of patriotism and nationalism, actively involved nature community empowerment through da'wah activities, education, social, religious and military. Their involvement in practical politics and community empowerment has implications for progress in South Sumatra. This study deconstructs collective perceptions and memories that assume that scholars should not engage in practical politics, since practical politics do not represent morality and honesty, a condition with ambition and avarice that is contrary to Islamic shari'a.